2021
DOI: 10.1016/j.isci.2021.103394
|View full text |Cite
|
Sign up to set email alerts
|

Cryogenic electron microscopy reveals that applied pressure promotes short circuits in Li batteries

Abstract: Summary Li metal anodes are enticing for batteries due to high theoretical charge storage capacity, but commercialization is plagued by dendritic Li growth and short circuits when cycled at high currents. Applied pressure has been suggested to improve morphology, and therefore performance. We hypothesized that increasing pressure would suppress dendritic growth at high currents. To test this hypothesis, here, we extensively use cryogenic scanning electron microscopy to show that varying the applied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 72 publications
1
20
0
Order By: Relevance
“…However, the impacts of applied pressures on the electrochemical performance of Li metal pouch cells are more complex depending on the electrolyte systems and charging-discharging processes. [70,71] Wang et al probed the effect of external pressure on the plating and stripping processes of Li metal anode with Li 7 P 2 S 8 Br 0.5 I 0.5 electrolyte. [67] It was found that the pressure required in the stripping process is positively related to the critical current density (the maximum current density at which dendrite penetration is suppressed), while higher pressure results in lower critical current densities in the plating process (Figure 3e).…”
Section: Pressure Distributionmentioning
confidence: 99%
“…However, the impacts of applied pressures on the electrochemical performance of Li metal pouch cells are more complex depending on the electrolyte systems and charging-discharging processes. [70,71] Wang et al probed the effect of external pressure on the plating and stripping processes of Li metal anode with Li 7 P 2 S 8 Br 0.5 I 0.5 electrolyte. [67] It was found that the pressure required in the stripping process is positively related to the critical current density (the maximum current density at which dendrite penetration is suppressed), while higher pressure results in lower critical current densities in the plating process (Figure 3e).…”
Section: Pressure Distributionmentioning
confidence: 99%
“…Meanwhile, the PPC1200 cell with a bare polyethylene (PE) separator experienced a sudden voltage drop at the charge end during the 156 th cycle (Figure c). Recently, Kanamori et al and Harrison et al , demonstrated that although the application of high external pressure (>1 MPa) affords the dense Li deposition, an excess compressive pressure could cause a short circuit, rather than its inhibition, during repeated stripping/plating in Li||Cu cells, thus decreasing the cycle life of Li metal cells. Figure S8 shows that the facile application of a commercially available boehmite dual-coated PE separator improved the stability of the Li metal anode by preventing short circuits.…”
mentioning
confidence: 99%
“…Applied stack pressures on the order of the flow stress of lithium metal can promote interface stability in liquid, 4,10 and solid-state cells, 6 but negative effects of stack pressure have also been noted. 11 At low to moderate plating current densities in liquid cells, the dominant type of filaments are needle-shaped "whiskers," or dense clusters of whiskers termed "moss". This regime of current density is of significant interest for battery applications.…”
mentioning
confidence: 99%